Peningkatan Kualitas Pelayanan Surat Izin Mengemudi Pada Kantor Satlantas Polres Kota Kendari - Firnanda, Amand; Yusuf, Muhammad; Manguntara, La (Universitas Halu Oleo, 2021)
The purpose of this study is to determine the quality of service in the management of SIM C and what factors affect the quality of service at the Kendari City Police Traffic Unit. The sources of this research, the study determined 6 (six) informants consisting of Deputy Chief of Police, Operations Section, Resources Section , General Section, and 2 (two) Service Users. The research method used is descriptive with a qualitative approach. Data collection techniques used in the form of interviews, observation and documentation. The results showed that the service quality of employees at the Kendari City Satlantas Police Office in carrying out SIM management services as a whole had been implemented well. The stages of service are not too complicated, so that people can take care of their SIM quickly and easily. However, there are still some things that need to be addressed, such as increasing the competence of SIM management officers and facilities that support service quality. While the factors that affect the quality of service at the Sarlantas Polres Kendari City, such as internal factors which include the motivation and work ethic of service officers that have been implemented properly, this is realized by friendly service and the community is treated well. While external factors, there are several problems, namely the number of officers who are still lacking, causing a lack of efficiency in services and facilities such as hardware that is prone to errors, this of course has a huge impact on the quality of services provided.